Repayment of co-using fertilizers and foliar nutrition biopreparations on crops of winter wheat in the Southern Steppe of Ukraine - Gamaiunova , V. V.; Panfilovа , A. V. (Scientific Progress & Innovations, 2019)
The purpose of the work was improving the elements of the cultivation technology of winter wheat varieties in the conditions of the Southern Steppe of Ukraine on the basis of resource-saving plant nutrition by treating the plants with the growth-regulating preparations during the main vegetation periods on the background of the main applying low doses of mineral fertilizers. Methods of research. Experimental studies were conducted during 2011–2016 in the experimental field of Mykolaiv NAU. The objects of the research were such winter wheat varieties as Kolchuha and Zamozhnist. Generally accepted methods for the given research area were used in the experiments. The yield was determined by the method of overall mowing from each accounting area. The research results. The studies have shown that, over the years of the research, the winter wheat yield of Kolchuha variety was 2.89–4.48 t/ha, and the yield of Zamozhnist variety was 3.05–4.99 t/ha, depending on the variant of nutrition. The most effective variant of crop nutrition, over the years of research, was the application of a moderate dose of mineral fertilizers and additional fertilization during the vegetation period with the preparations “Organic D2” and “Escort-bio”. Thus, using these nutrition variants has resulted in yield increasing of Kolchuha winter wheat variety to 25.50–26.50 kg, and of Zamozhnist variety – to 31.83–32.33 kg. The elements of scientific novelty. The questions of the resource-saving nutrition of winter wheat plants, in connection with the appearance of new varieties, preparations and changes of climatic and soil conditions have been considered. The practical significance of the obtained results is the development, improvement and introduction into production of the elements of winter wheat cultivation technology in the Southern black soil, as this crop provides grain yield growth at the level of 1.59–1.94 tons/ha depending on the variety.